Bunnicula : a rabbit-tale of mystery - Howe, Deborah; Howe, James, 1946-; Daniel, Alan, 1939- (New York : Atheneum Books for Young Readers, 2004)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire.
"25th anniversary edition"--Dust jacket.
8
Keywords: Rabbits -- Fiction; Vampires -- Fiction; Mystery and detective stories